Integrating morphology with phylogenomics to describe four island endemic species of Temnothorax from Sicily and Malta (Hymenoptera, Formicidae) - Schifani, Enrico; Prebus, Matthew M.; Alicata, Antonio (European Journal of Taxonomy, 2022)
Temnothorax (Myrmicinae, Crematogastrini) is one of the most diverse Holarctic ant genera, and new taxonomic advancements are still frequent worldwide. The Mediterranean region, a global biodiversity hotspot characterized by a complex geographic history, is home to a substantial portion of its described diversity. Sicily is the region’s largest island and, as ongoing investigations are revealing, it is inhabited by a long-overlooked but highly diverse ant fauna that combines multiple biogeographic influences. We combined qualitative and quantitative morphology of multiple castes with phylogenomic analysis based on ultra-conserved elements (UCEs) to describe four species of Temnothorax endemic to Sicily and the neighboring Maltese Islands (Sicilian Channel). Three of these species, T. marae Alicata, Schifani & Prebus sp. nov., T. poldii Alicata, Schifani & Prebus sp. nov. and T. vivianoi Schifani, Alicata & Prebus sp. nov., are new to science, while a redescription clarifies the identity of T. lagrecai (Baroni Urbani, 1964). These descriptions highlight the current difficulties of delimiting monophyletic Temnothorax species groups based on morphological characters. The intra-insular endemicity patterns we revealed highlight the importance of Mediterranean paleogeography to contemporary ant diversity and distribution in the region.